Biomimetic Design and Fabrication of Sericin-Hydroxyapatite Based Membranes With Osteogenic Activity for Periodontal Tissue Regeneration - Ming, Piaoye; Rao, Pengcheng; Wu, Tianli; Yang, Jianghua; Lu, Shi; Yang, Binbin; Xiao, Jingang; Tao, Gang (Frontiers in Bioengineering and Biotechnology, 2022)
The guided tissue regeneration (GTR) technique is a promising treatment for periodontal tissue defects. GTR membranes build a mechanical barrier to control the ingrowth of the gingival epithelium and provide appropriate space for the regeneration of periodontal tissues, particularly alveolar bone. However, the existing GTR membranes only serve as barriers and lack the biological activity to induce alveolar bone regeneration. In this study, sericin-hydroxyapatite (Ser-HAP) composite nanomaterials were fabricated using a biomimetic mineralization method with sericin as an organic template. The mineralized Ser-HAP showed excellent biocompatibility and promoted the osteogenic differentiation of human periodontal membrane stem cells (hPDLSCs). Ser-HAP was combined with PVA using the freeze/thaw method to form PVA/Ser-HAP membranes. Further studies confirmed that PVA/Ser-HAP membranes do not affect the viability of hPDLSCs. Moreover, alkaline phosphatase (ALP) staining, alizarin red staining (ARS), and RT-qPCR detection revealed that PVA/Ser-HAP membranes induce the osteogenic differentiation of hPDLSCs by activating the expression of osteoblast-related genes, including ALP, Runx2, OCN, and OPN. The unique GTR membrane based on Ser-HAP induces the differentiation of hPDLSCs into osteoblasts without additional inducers, demonstrating the excellent potential for periodontal regeneration therapy.